Asset Pricing Investigation of Chinese SMEs: A Multi-Factor Model Approach - Yuan, Yue (2019)
The paper investigates the applicability of multi-factor models by stock returns from January 2014 to June 2019 from the Chinese Shenzhen Small and Medium Enterprises Composite Board. It fills the research gap that researches of multi-factor models on the small and medium-sized enterprises are limited. The purpose of the study is to find the model with the highest fitness and to give suggestions to investors and portfolio managers. By comparing the performance of the three-factor model, the four-factor model, and the five-factor model, the test concludes that the four-factor model performs the best in Chinese stock market, and the five-factor model is the worst. Specifically, the stock price of small and medium-sized enterprises is largely affected by the previous stock performance but is weakly related to companies’ profitability and investment capability. The result is inconsistent with previous studies in the US stock market (Fama and French, 2015) and the mainboard in Chinese stock market (Lin, 2017) supporting that the five-factor model is better than the three-factor model as well as the four-factor model. Additionally, the value factor and the size factor are found redundant in the four-factor model, implying that excess returns are exposed to the momentum factor.